Uterine procidentia in a virgin woman: A rare case - Nastaran Mahmoudnejad; Alvand Naserghandi; Qumars Kasnavi; Mohammad Amin Tofighi Zavareh (Urology Case Reports)
Uterine prolapse in virgin females is extremely rare. In this case study, we present a 65-year-old virgin female patient who experienced voiding difficulties and uterine prolapse. She did not have any preexisting medical conditions, and all laboratory tests came back normal. We will discuss the surgical procedure performed, the patient's follow-up course and provide a brief review of the existing literature.